Stylodactylidae and Bathypalaemonellidae (Crustacea: Decapoda: Caridea) from the PANGLAO 2004 and 2005 expeditions to the Philippines, with description of a new species of Stylodactylus A. Milne-Edwards, 1881 - Cleva, Régis (Zootaxa, 2008)
Five species of the family Stylodactylidae Bate, 1888 and two species of Bathypalaemonellidae de Saint Laurent, 1985, were collected by the PANGLAO 2004 and 2005 expeditions to the Philippines. A member of the Stylodactylidae, Stylodactylus gracilis new species, collected at 2149–2217 m, is described and illustrated. The new species is distinguished from the 15 described species of Stylodactylus by a very thin and glabrous integument; a very long (0.8 times of carapace length) antennular peduncle, by the lengthening of the second segment (1.8 times longer than first); thin and very long third to fifth pereopods, as a result of the lengthening of the meri and propodi . The two species of Bathypalaemonellidae, Bathypalaemonella aff. hayashii Komai, 1995, and Bathypalaemonetes brevirostris (Bruce, 1986), represent new records for the Philippines.